Activation and Evasion of RLR Signaling by DNA Virus Infection - Jia, Junli; Fu, Jiangan; Tang, Huamin (Frontiers in Microbiology, 2021)
Innate antivirus immune response triggered by nucleic acid recognition plays an extremely important role in controlling viral infections. The initiation of antivirus immune response against RNA viruses through ligand recognition of retinoic acid-inducible gene I (RIG-I)-like receptors (RLRs) was extensively studied. RLRs roles in DNA virus infection, that is less known, is starting to gain increasing attention. Here, we review the research progress of the ligand recognition of RLRs during DNA virus infection process, and the viral evasion mechanism from host immune responses.